2D Elemental Nanomaterials Beyond Graphene. Issue 9 (17th June 2019) - Vishnoi, Pratap; Pramoda, K.; Rao, C. N. R.
Abstract: Graphene is a well‐known 2D material with potential applications. In recent years, 2D materials of other elements have come to the fore. These are borophene in group III, silicene, germanene and stanene in group IV and phosphorene, arsenene, antimonene and bismuthene in group V. In this article, we discuss the synthesis, structure and properties of the elemental 2D materials beyond graphene. Of the various elemental 2D materials, borophene, silicene and phosphorene are interesting in terms of stability and properties leading to possible applications. We have described potential applications of other 2D materials as well. Abstract : Elementary, my dear Watson : The 2D nanomaterials formed by group‐III, IV and V are of considerable interest due to their attractive structural and electronic properties. In this review, the recent progress on the synthesis, structure, properties and applications of these elemental 2D nanomaterials is presented.